Genetic parameters of plasma and ruminal volatile fatty acids in sheep fed alfalfa pellets and genetic correlations with enteric methane emissions. (19th June 2019) - Jonker, Arjan; Hickey, Sharon M; McEwan, John C; Rowe, Suzanne J; Janssen, Peter H; MacLean, Sarah; Sandoval, Edgar; Lewis, Sarah; Kjestrup, Holly; Molano, German; Agnew, Michael; Young, Emilly A; et al.
Abstract: Animal-to-animal variation in methane (CH4 ) emissions determined in respiration chambers has a genetic basis, but rapid phenotyping methods that can be applied on-farm are required to enable increased genetic progress by the farming industry. Fermentation of carbohydrates in the rumen results in the formation of VFA with hydrogen (H2 ) as a byproduct that is used for CH4 formation. Generally, fermentation pathways leading to acetate are associated with the most H2 production, less H2 formation is associated with butyrate production, and propionate and valerate production are associated with reduced H2 production. Therefore, VFA may constitute a potential correlated proxy for CH4 emissions to enable high-throughput animal screening. The objective of the present study was to determine the genetic parameters for ruminal and plasma VFA concentrations in sheep fed alfalfa ( Medicago sativa L.) pellets and their genetic ( r g ) and phenotypic ( r p ) correlations with CH4 emissions. Measurements of CH4 emissions in respiration chambers and ruminal (stomach tubing 18 h from last meal) and blood plasma (3 h post-feeding) VFA concentrations were made on 1, 538 lambs from 5 birth years (2007 and 2009 to 2012) aged between 5 and 10 mo, while the animals were fed alfalfa pellets at 2.0 times maintenance requirements in 2 equal size meals (0900 and 1500 h). These measurements were repeated twice (rounds) 14 d apart. Mean (± SD) CH4 production was 24.4 ± 3.08 g/d, and the mean CH4 yield was 15.8 ± 1.51 g/kg DMI. Mean concentration of total ruminal VFA was 52.2 mM, with concentrations of acetate, propionate and butyrate of 35.97, 8.83, and 4.02 mM, respectively. Ruminal total VFA concentration had heritability ( h 2 ) and repeatability estimates (± SE) of 0.24 ± 0.05 and 0.35 ± 0.03, respectively, and similar estimates were found for acetate, propionate, and butyrate. Blood plasma concentrations of VFA had much lower estimates of h 2 and repeatability than ruminal VFA. Genetic correlations with CH4 yield were greatest for total concentrations of ruminal VFA and acetate, with 0.54 ± 0.12 and 0.56 ± 0.12, respectively, which were much greater than their corresponding r p . The r p and r g of ruminal VFA proportions and blood VFAs with CH4 emissions were in general lower than for ruminal VFA concentrations. However, minor ruminal VFA proportions had also moderate r g with CH4 yield. Pre-feeding concentrations of total VFA and acetate were the strongest correlated proxies to select sheep that are genetically low CH4 emitters.